Drill phobia. - Prendergast, Ben (American Enterprise, 2001)
Oil and gas drilling represent an important source of future energy supplies in the U.S. For example, the Arctic National Wildlife Refuge is thought to be a significant oil reserve, although environmental opponents are seeking to cut funds that President George W. Bush has asked for to carry out a study of the area. Despite this, oil drilling is not the ecological nightmare that it can be described as, and oil production is being carried out in wildlife refuges across the U.S. Such an ideology of refusing to make sensible compromises with the energy requirements of an advanced society may be endangering the standard of living that Americans enjoy and precipitating another energy crisis.